Analysing sovereign credit default swaps of Baltic countries - Kregzde, Arvydas; Murauskas, Gediminas (Business: Theory and Practice, 2015)
The paper analyses development of the Baltic sovereign CDS market. The level of commonalities and differences in credit risk of the Baltic countries with regard to CDS spreads is investigated. We apply principal component analysis, regression analysis, correlation analysis methods and Granger causality test. Driving forces for changes of CDS spreads in the individual country are established. We discover that the main impact of CDS spread changes arrives from external sources. Our study reveals interdependence between CDS spreads of the Baltic countries and analyses a contagion effect of the change of CDS spreads.